Excellent Rate and Low Temperature Performance of Lithium‐Ion Batteries based on Binder‐Free Li4Ti5O12 Electrode. Issue 3 (3rd February 2020) - Hu, Bingqing; Zhou, Xiaoshuang; Xu, Jiang; Wang, Xi; Yuan, Ningyi; Ge, Shanhai; Ding, Jianning
Abstract: Achieving lithium‐ion batteries (LIBs) with ultrahigh rate at ambient‐temperature and excellent low temperature‐tolerant performances is still a tremendous challenge. In this paper, we design a binder‐free Li4 Ti5 O12 (LTO) electrode to achieve an excellent rate performance (∼75 % of its theoretical capacity at 200 C), in which, aligned CNT nanosheets were used to load LTO nanosheets decorated with silver nanocrystals. With combination of 1, 3‐Dioxlane‐based electrolyte, there is nearly no initial voltage drop happen, and the capacity can be greater than 140 mAh g −1 (∼85 % of its specific capacity at room temperature) at −60 °C and 0.2 C. This study provides a practical guidance of the design of LIBs with outstanding rate performances and low temperature resistance. Abstract : A binder‐free electrode with aligned CNT nanosheets as an alternative binder is designed to increase the utilization rate of nano active materials. With combination of 1, 3‐Dioxlane‐based electrolyte, lithium‐ion battery shows nearly no initial voltage drop and the capacity is more than 140 mAh g −1 at −60 °C and 0.2 C.